Polysaccharide/protein nanomultilayer coatings: construction, characterization and evaluation of their effect on 'Rocha' pear (Pyrus communis L.) shelf-life - Medeiros, Bartolomeu G. de S. (2012)
Nanolayered coatings of κ-carrageenan, a polysaccharide with good gas barrier properties, and lysozyme, a protein with antimicrobial action, were in a first stage assembled on aminolysed/charged polyethylene terephthalate (PET) pieces, which acted as a support, by alternate five-layer deposition. This was performed to allow the characterization of the nanomultilayer system. PET aminolysis was confirmed by Fourier transform infrared spectroscopy and contact angle, and the subsequent layer adsorption on aminolysed PET surface was confirmed by absorbance, contact angle and SEM images. The water vapour permeability and the oxygen permeability (O2P) of the five layers were found to be 0.013 ± 0.003 × 10−11 and 0.1 ± 0.01 × 10−14 g m−1 s−1 Pa−1, respectively. The nanomultilayer system was subsequently applied (without PET support) directly on ‘Rocha’ (Pyrus communis L.) fresh-cut pears and whole pears. Uncoated fresh-cut pears and whole pears presented higher mass loss, higher total soluble solids (TSS) and lower titratable acidity when compared with coated fresh-cut pears and whole pears. Uncoated fresh-cut pears also presented a darker colour. These results showed that the nanolayered coating assembled on the fruits’ surface has a positive effect on fruit quality and contributed to extend the shelf-life.